Will Russia Rule the World Through AI?: Assessing Putin's Rhetoric Against Russia's Reality. Issue 5 (19th September 2019) - Dear, Keith
Abstract : In this article, Keith Dear reviews the current state and future prospects of artificial intelligence (AI) research, development and application in Russia. He shows that the available socio-economic indicators suggest that, contrary to the Kremlin's aspirations, neither Russia's limited commercial software base, nor its not-dominant state-controlled tech R&D sectors are likely to be able to support Russia's AI ambitions. Across a range of measures – from its start-up ecosystem, supercomputing installations, electronics industry, once-great educational system, industrial base and business climate – the fundamentals on which AI R&D success would be built are weak and weakening in Russia.